The necessity of the refurbishment at the shopping complex from the customers' points of view case study: Kompleks Teruntum, Kuantan,Pahang Darul Makmur / Mastura Musa - Musa, Mastura (2010)
In Malaysia, refurbishment project is considered as a new phenomenon. Refurbishment is mainly conducted to the building which is considered as an old building. Scope of refurbishment refers to the work carried out on the existing building in the attempt to improve and to update it to modern standard whilst retaining its current use. Refurbishment for the old shopping complex is very important. The necessity of the refurbishment of the shopping complex exists because of the indirect and direct causes. The problems here are the decrease in terms of the number of the customers and also the potential buyers, the decrease in the percentage of the occupancy rate and the performance of the building. The objectives of the refurbishment are to attract customers and tenant, to give new image to the building, to put the building at same level with the new shopping complex, to extend the economic life span and as an investment. The main objectives of this project are firstly to identify the parts of the building that need to be considered to undergo the refurbishment, while the second is to identify the requirement of the refurbishment works from customer's point of view and the third objective is to identify the significance of refurbishment by referring to the shopping complex. The questionnaires form was distributed to the customers of the Kompleks Teruntum which is the target group of this study. From the analysis which is based on the ascending mean that has been done notice that the parts of the building that need to undergo refurbishment which are the lobby, air-conditioning system, exterior finishes, floor finishes, interior finishes, lighting system, escalator and ceiling finishes. This study concluded from the analysis that has been done proven that the proposed refurbishment is viable or beneficial because it provides good returns in the future.